ANALISIS FAKTOR YANG MEMPENGARUHI PELAPORAN INSIDEN KESELAMATAN PASIEN DI RS MATA JEC-CANDI, SEMARANG - Uswatunnisa Arfiningtyas; Djasri, Hanevi; Bismantara, Haryo (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2025)
Background: The Patient Safety Incident (PSI) reporting system is a recommended method for enhancing patient safety, and it has been implemented by hospitals. However, the reporting rate of PSI remains low. Objectives: This study aims to analyze the impact of individual, team, and organizational factors on PSI reporting at JEC-Candi, Semarang eye hospital and to develop recommendations to improve PSI reporting. Methods: A mixed-methods sequential explanatory design was used. Quantitative data were obtained through a cross-sectional questionnaire survey and analytical observations using secondary data. Qualitative data were gathered from focus group discussion (FGD) with four separate groups: daily practitioner doctors, daily practitioner healthcare workers, daily practitioner non-healthcare workers, and managerial staff. Quantitative data were analyzed using chi-square or Fisher's exact tests and multivariate logistic regression, while qualitative data were analyzed using thematic analysis. Results: The study involved 85 subjects for the quantitative study and 25 subjects for the qualitative study. Individual factors (knowledge and motivation), team factors (teamwork), and organizational factors (feedback) significantly influenced PSI reporting (p<0.005). Motivation emerged as the most dominant factor influencing PSI reporting (p=0.008; OR 47.294; CI 95% 2.678-835.190). The qualitative results provided several recommendations for improving PSI reporting, including regular socialization and training, patient safety awareness campaigns, selecting patient safety champions, establishing reward and incentive systems, organizing team-building and cross-unit collaborative activities, and improving access to PSI reporting feedback information. Conclusions: Individual, team, and organizational factors significantly influence PSI reporting. Therefore, management should implement the recommended strategies to enhance patient safety and quality in the hospital.